The validation of the mid-upper arm circumference measurement in adults as a weight estimation tool in a high HIV prevalence setting - Chen, Emily (Division of General Surgery, 2023)
Background Accurate weight estimation in emergency centres is important to ensure accurate treatment and limit adverse outcomes. The mid-upper arm circumference (MUAC) as a weight estimation tool has recently expanded to adults. The MUAC's ease of use and cost effectiveness could be beneficial to estimate the weight of sick, adult patients presenting to emergency centres. The objectives were to assess correlation between MUAC and both weight and body mass index (BMI) in adults, externally validate an existing MUAC-based weight estimation formula in a high HIV prevalent emergency centre, and if inaccurate, to derive a MUAC-based weight estimation formula more suitable to the adult study population. Methods A cross-sectional diagnostic study was done in the emergency centre of Khayelitsha hospital, South Africa. Anthropometric data (MUAC, weight and height) and HIV status were obtained from consecutive adult (≥18 year) participants. Correlation of MUAC with weight and BMI were determined using Spearman's correlation coefficient with 95% confidence intervals in all participants and in HIV positive participants. Predicted weights were calculated from previously developed formulae (regression formula: kg=(3.8484×MUAC)−46.8585; simplified formula: kg=(4×MUAC)−50). The agreement between the predicted and observed weights were graphically assessed with a calibration plot. Linear regression was used to derive a MUAC-based formula in the study population. Results A total of 244 participants (median age = 37 years; 111 male) were included, of whom 121 (49.6%) were HIV positive. The correlation between MUAC and weight was 0.93 (HIV positive 0.92), and between MUAC and BMI 0.93 (HIV positive 0.94). The regression formula predicted weight within 10%, 20% and 30% of actual weight in 43.9%, 77.5% and 90.2% of all participants and 33.1%, 69.5% and 85.1% in HIV positive participants. The simplified formula predicted weights within 10%, 20% and 30% of actual weight in 46.7%, 77.5% and 89.8% of all participants and in 35.5%, 70.2% and 85.1% in HIV positive participants. The locally derived formula (kg=(3x MUAC) -16) better estimated weight in the local population.